Find the composite function (f o g)(x) and simplify the results

Find the composite function (f o g)(x) and simplify the results

Find thhe function F(x) given that f of g(x) is 1/6x^2 and g(x)=3x^2-2

a) f(x) = 2x+3 g(x) = x-3/2 f(g(x))= ? g(f(x))= ? f and g are inverses of each other OR f and g are not inverses...

For the given functions f and g , find the indicated composition

g(n) = 3n + 2 f(n) = 2n2 + 5 find g(f(2))

how do you start the problem because I am having difficulty starting it off

Example:p(t_ = 2t - 1 and q(t) = -t2 - 4t - 1. Find (q - p)(t) (q - p)(t) = q(t) - p(t) q(t) - p(t) "define" (-t2 - 4t - 1) - (2t - 1) "substitute" =(-t2...

Given the following functions calculate g(f(14)) f(x)=1/(x−11) g(x)=1/x

Find functions f and g such that h = g ∘ f. (Note: The answer is not unique. Enter your answers as a comma-separated list of functions. Use non-identity functions for f and g.) h(x) =...

f(x) = x^2 - 7 g(x) = sqrt(20 - 5 x) (f o g)(x) =? The domain of (f o g)(x) is ?

given f(x)=4x^3-x and g(x)= x^2-5x-13 evaluate f(bracket)g(6)(bracket)

f(x) = 2 x - 4 g(x) = x^2 - 3 x + 2

f(x) = x/x+1 g(x) = 10/x (f o g)(x) =

f(x) = 7sqrt{x} g(x) = x - 11 (f o g)(x) =

Answers: 1. 4a^2-a+6 2. 4a^2-a+4 3. 4a^2+7a+6 4. 4a^2+7a+4

f(x) = 4 - x g(x) = 3 x^2 + 2 x - 6 (f o g)(x) = (g o f)(x) = (f o g)(-2) =

f(x) = 9sqrt{x} g(x) = x + 11 (f o g)(x) = (g o f)(x) = (f o g)(5) =

f(x) = 5 x g(x) = 9 x - 2 (f o g)(x) = (g o f)(x) = (f o g)(-3) =

Let f(x) = 6x2+7 and g(x) = x-3 a) Find the composite function (f°g)(x) and simplify. b) Find (f°g)(-1) Okay so if I am understanding this...

Let f (x) = 3x2+ 7 and g(x) = x – 4. (a) Find the composite function ) ( f o g)(x and simplify. (b) Find ( f o g)(− )1 .